A comparative Study on the Average Cumulative Mortality Rate of Oreochromis niloticus Fingerlings Reared with Sublethal Concentrations of Zinc, Copper and Mercury, Singly or in Combination - Goc-ong Tobias, Ermelinda; B. Tobias Jr., Daniel; S. Cariño, Virginia (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
I Preliminary bioassays of the three heavy metal salts such as zine sulfate (2nS04.7H20), copper sulfate (CuSO4.5H20) and mercuric chloride (HgCI2) were performed on Oreochromis niloticus fingerlings and were estimated as 25 mg/l, 2.857 mg/ land 0. 833 mg/l, respectively. Sublethal concentrations of these metals were used to treat the water media singly or in combinations where the fingerlings were reared for 30 days. Daily mortality was recorded and average cumulative mortality rate during the two successive 15 days were computed. Results showed that copper in the concentration used was the most toxic and it acted synergistically with the zinc and mercury.